Bird abundance and habitat quality in a monoculture oil palm plantation - Mohamad Zulzurin, Siti Aisyah (2016)
Forest biodiversity in the tropics is now experiencing dramatic landscape changes due to the expansion of oil palm plantation which is caused by the pressure from economic growth and increasing population. This paper describes how the vegetation, structural complexity and weeding practice affect bird abundance in an oil palm plantation. The main objective of this study was to examine which habitat quality parameters influence bird abundance the most in an oil palm plantation. The study was conducted in the 54 ha UPM oil palm plantation where a total of 20 point count stations were established in three types of oil palm plantation (immature, mature and old) plantation. A total of 1023 individual from 21 species of birds were recorded throughout the study. This study revealed that bird abundance was influenced by canopy cover, followed by age of oil palm stands, treatment (weeding), height of oil palm, season (wet/dry) and also the non grass height. However grass and non grass cover and grass height had no significant effects on bird abundance. The bird abundance increases as the canopy cover decreases. The increase in oil palm age and height leads to an increase in bird abundance. In addition, the presence of weeding activity and wet season cause bird abundance to decrease. Overall, these significant parameters play important role as the key habitat qualities that influence bird abundance in a monoculture oil palm plantation.